Pengaruh Pengawasan Kerja dan Penerapan Sistem Absensi Fingerprint Terhadap Produktivitas Kerja pada Guru MAN 1 Kota Bekasi - Safina Tunnajah; Tyna Yunita; Tungga Buana Irfana; Hasanuddin Hasanuddin; Franciscus Dwikotjo Sri Sumantyo (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to test and analyze the effect of supervision and implementation of a fingerprint attendance system on work productivity among MAN 1 teachers in Bekasi City. The research method used in the research is quantitative methods. The collection technique in this research used observation and distributing questionnaires to 101 teachers in Bekasi City who were used as respondents. The sampling technique in this research used a saturated sampling technique. The data analysis technique in this research uses descriptive and SmartPls 4.0. The results of this research show that there is a significant influence between supervision (X1) on work productivity (Y) = 0.290 (Tstatistics 2.143 > Ttable 1.96). There is a significant influence between fingerprint absence (X2) on work productivity (Y) =0.559 (Tstatistics 5.241 > Ttable 1.96). There is a significant influence between supervision (X1) on fingerprint attendance (X2) = 0.670 (Tstatistics 5.576 > Ttable 1.96). And finally Fingerprint absence (X2) mediates between supervision (X1) and work productivity (Y) = 0.375 significantly (Tstatistics 4.211 > Ttable 1.96).